THU0486 2019 FRENCH GUIDELINES AND CARE PATHWAY ABOUT LOW BACK PAIN MANAGEMENT IN ADULTS. (2nd June 2020) - Bailly, F.; Trouvin, A. P.; Bercier, S.; Dadoun, S.; Deneuville, J. P.; Faguer, R.; Fassier, J. B.; Koleck, M.; Lassalle, L.; Le Vraux, T.; Liesse, B.; Petitprez, K.; et al.
Abstract : Background: Low back pain (LBP) is a frequent, disabling symptom, for which the risk of chronicity is increased by heterogeneous care. Developing and implementing recommendations is likely to improve LBP management. Objectives: To develop French guidelines and care pathway on the management of LBP, coordinated by the French National Authority for Health (FNAH) and based on previous international guidelines in addition to update literature. Methods: A compilation report was constituted on the basis of a systematic review of guidelines between January 2013 and December 2018, and systematic reviews and meta-analysis in the field of LBP between January 2015 and December 2018. This report summarized the state-of-the-art for each predefined area of the guideline. A panel of experts including patients' representatives and 19 health professionals involved in LBP management was constituted to elaborate the guideline based on the compilation report. A care pathway was constituted to identify the trajectory and the different steps followed by a patient with LBP. Then, the compilation report and the preliminary guidelines were submitted to 24 academic institutions and stakeholders for feedback. Based on the preliminary guideline and the responses of academic institutions and stakeholders, the final recommendations were drawn up by the expert panel. The guideline was finally submitted to an independent committee of the FNAH for final validation. For each area of the guidelines, agreement between experts of the working group was evaluated through the RAND/UCLA method. Results: The initial literature search identified 572 references of recent international guidelines or systematic reviews about LBP. After selection, the compilation report included 101 references. The compilation report was submitted to the expert group during 3 different meetings to reach a consensus on different topics. Thirty-one preliminary recommendations and a care pathway (divided in two parts to facilitate its use and readability) were drafted and submitted to academic institutions and stakeholders. Having considered their comments, final recommendations and care pathway were written. The final guideline was validated by the FNAH. Then, the consensus of the expert panel was assessed about all the final guidelines separately: 32 recommendations (including the care pathway) were evaluated as appropriate; none were evaluated uncertain or inappropriate. Strong approval was obtained for 27 of them (including the care pathway) and weak for 5 of them. Conclusion: This new LBP guideline was based on recent scientific evidence. It introduced several concepts, including the need to identify low back pain at risk of chronicity, in order to provide quicker intensive management if necessary. This guideline should be updated in 5 years' time, in order to keep it in line with ongoing scientific evidence. Disclosure of Interests: Florian Bailly Consultant of: Consultation fees from Lilly and Grünenthal laboratories, Anne Priscille Trouvin Speakers bureau: Speaker for menarini, recordati, pfizer, astellas, Sandrine Bercier: None declared, Sabrina Dadoun: None declared, Jean Philippe Deneuville: None declared, Rogatien Faguer: None declared, Jean Baptiste Fassier: None declared, Michèle Koleck: None declared, Louis Lassalle: None declared, Thomas Le Vraux: None declared, Brigitte Liesse: None declared, Karine Petitprez: None declared, Aline Ramond: None declared, Jean François Renard: None declared, Alexandra Roren: None declared, Sylvie Rozenberg Consultant of: Pfizer, Catherine Sebire: None declared, Gilles Viudes: None declared, François Rannou Grant/research support from: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Fondation Arthritis, Consultant of: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Genévrier, Speakers bureau: Pierre Fabre, Fidia, MSD, Pfizer, Bone Therapeutics, Expanscience, Grunenthal, Thuasne, Audrey Petit: None declared